ANALISIS PENGARUH TATA KELOLA, KARAKTERISTIK PERUSAHAAN DAN STRUKTUR KEPEMILIKAN TERHADAP KINERJA KEUANGAN PERUSAHAAN LQ45 YANG TERDAFTAR DI BEI - Sunarjanto, Nekhasius Agus; Tananjaya, Tania Oktavianes; Martono, Cyrillius (Media Mahardhika, 2024)
This study investigates the influence of governance, company characteristics, and ownership structure on the financial performance of LQ45 companies listed on the IDX during the 2018-2022 period. Governance is represented by agency costs and free cash flow, while company characteristics include company size and company age. Ownership structure consists of managerial ownership, institutional ownership, and public ownership. The financial performance is proxied by Tobin's Q. The research employs a quantitative method, utilizing panel data analysis with the fixed effect model as the selected approach. Secondary data collection was conducted using documentation methods, and the sample was selected through purposive sampling, totaling 100 data points. The results indicate that free cash flow, managerial ownership, and institutional ownership do not significantly affect financial performance. However, agency costs, company size, company age, and public ownership have a significant effect on financial performance.